Hallazgos en la coherencia cerebral en caninos con comportamiento agresivo - Rivero, J.E. (2008)
We used the interhemispheric coherence to investigate the difference between normal and aggressive dogs in base to quantify the base line of electroencephalogram. Dorsal and temporal group was defined by significant statistic difference in the frequency\nspectrum. Temporal channels showed low interhemispheric coherence and phase delay in aggressive dogs. Coherence is an easy and noninvasive technique capacious to proved and quantified alteration in electroencephalogram base line.